Hazy Bloom and the mystery next door - Hamburg, Jennifer; Harney, Jennifer (Farrar Straus Giroux, 2019)
"When Hazy Bloom gets a tomorrow vision of a ghost flying around the empty house next door, her boring summer vacation suddenly takes a mysterious, thrilling, and hilariously Hazy-like turn"--
Keywords: Extrasensory perception -- Fiction; Haunted houses -- Fiction; Family life -- Fiction; Humorous stories